Application of optical fiber sensing technology in similar model test of Shallow-buried and thick coal seam mining. (August 2021) - Du, Wengang; Chai, Jing; Zhang, Dingding; Lei, Wulin
Highlight: The phenomenon of large and small period weighting of overburden is analysed. The stress state of fiber in mining overburden is analyzed. Five kinds of mining overburden media in contact with optical fiber are proposed. Strain growth rate based on optical fiber sensing is proposed. Abstract: In order to study the deformation law and internal stress evolution characteristics of overlying strata after shallow and thick coal seam mining, a physical similarity model with geometric size of 1500 × 1300 × 600 mm is designed and constructed. Distributed optical fiber and fiber grating sensors are embedded in the model to monitor the deformation of overlying strata in the process of coal mining. The research shows that FBG measurement strains achieving its peak need to satisfy two conditions: the working face passes beneath it, and the cantilever beam structure above the working face collapses, and the grating is located at the end of the dangling clamped–clamped beam; After coal excavation, the stress of surrounding rock redistributes, the optical fiber is located in front of the working face and in the area affected by the leading abutment pressure. With the working face getting closer, the abutment pressure increases continuously, which leads to the step-by-step growth of the measured strain curve; The strain data have changed significantly when the working face underwent the large periodic weighting process, and the overall range and intensity of variation is much larger than the non-weighting and small periodic weighting mining process; The step of initial weighting is 49.5 m, and the average value of step in periodic weighting is 13 m; The mining affected zone detected by optical fiber sensor develops to a height of about 105 m from the coal seam, while the height of the fractured zone develops to 52.5 m from coal seam, and the height of mining affected zone is much higher than that of the fractured zone. The research results are of great significance for popularizing the application of optical fiber sensing technology in mining engineering field.